2011
DOI: 10.1007/s11144-011-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of the dehydration of d-xylose in high temperature water

Abstract: A kinetic model of the homogeneous conversion of D-xylose in high temperature water (HTW) was developed. Experimental testing evaluated the effects of operating conditions on xylose conversion and furfural selectivity, with furfural yields of up to 60% observed without the use of acid catalysts. The reaction order for the decomposition of D-xylose was assumed to be above two, while the conversion of D-xylose to furfural and the degradation of furfural were first order reactions. Estimated kinetic parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…values than those obtained here (Danon et al, 2014, Liu et al, 2014, Jing and Lü, 2007, which suggests that the effect of temperature observed herein is not as high as that reported in other studies. However, results regarding the same temperature range as in the present work led to lower E a , thus in agreement with our findings (Kim et al, 2011).…”
Section: Reaction Kineticssupporting
confidence: 94%
See 1 more Smart Citation
“…values than those obtained here (Danon et al, 2014, Liu et al, 2014, Jing and Lü, 2007, which suggests that the effect of temperature observed herein is not as high as that reported in other studies. However, results regarding the same temperature range as in the present work led to lower E a , thus in agreement with our findings (Kim et al, 2011).…”
Section: Reaction Kineticssupporting
confidence: 94%
“…In the recent past, the kinetics of FU production / decomposition competitive reactions (Marcotullio et al, 2009) were thoroughly studied for several biomasses or biomass-derived molecules such as wheat straw (Yemiş and Mazza, 2012) and xylose (Liu et al, 2014) submitted to HTC. Most works generally focused either on production or on decomposition reactions separately (Liu et al, 2014, Danon et al, 2014, Kim et al, 2011. Simple consecutive reaction models as well as models taking into account side reactions have been developed Lü, 2007, Liu et al, 2014) and are in agreement with published studies on degradation compounds from sugars (Rasmussen et al, 2014).…”
Section: Introductionmentioning
confidence: 85%
“…conversion. Most open literatures show various E a and K 0 values due to the wide range of reaction temperatures, durations and catalyst use (Danon et al, 2014;Kim et al, 2011;Liu et al, 2014).…”
Section: Individual Model Compounds Pathway During Htc Processmentioning
confidence: 99%
“…Furfural is conventionally produced by hydrolysis of a variety of biomass sources including almond shell, sugarcane, and corn with the aid of liquid acid catalysts at high temperatures (200-250°C) (Kim et al 2011). However, liquid acid catalysts are toxic and corrosive, and their applications can generate large amounts of toxic wastes.…”
Section: Introductionmentioning
confidence: 99%